Exploring Student Online Purchase Decision Patterns: A Global Perspective with Insights from Islamic Economics - Cindy Cantika Dwi Oktaviani; Davina Putri Ainny; Muhammad Rifky Fauzan; Sabrina Mustika (Higher Education Spiritual Pedagogies, 2023)
The purpose of this research is to find out how the behavior patterns are formed by students when making online shopping transactions, to see the relationship between the online shopping system and consumptive behavior that arises when shopping, and to see how Islam views consumptive behavior which is a phenomenon in the midst of this digital era. . The method used in this research is a descriptive survey in which this research takes a sample from a population, and uses a questionnaire as a data collection tool. The results of the study show that respondents who are UPI students in making purchasing decisions when shopping online, they make various considerations and are not reckless in buying goods online, with various considerations made starting from price, needs, to product reviews. In an Islamic perspective, the consumption behavior shown in the research results is within reasonable limits and does not violate various consumption restrictions as a Muslim because consumption that is respected by a Muslim is when they are modest and prioritize needs rather than wants